Code Mixing on Beby Tsabina TV: A Sociolinguistics Study of YouTube Content - Enny Nurhaliza; M. Manugeren; Idawati Situmorang (JOURNAL OF LANGUAGE, 2026)
This study analyses code-mixing in the YouTube content of Beby Tsabina, an Indonesian actress and content creator on her channel Beby Tsabina TV. Beby frequently mixes English and Indonesian in her videos, presenting a rich case of bilingual language use. Using a descriptive qualitative method, this research identifies types of code-mixing based on Marzona's (2000) theory and describes their functions based on Marzona's (2005) framework across three selected videos. The analysis reveals 14 instances of congruent lexicalization, 45 instances of insertion, and 47 instances of alternation. Functionally, the data show 4 instances of greetings, 31 of storytelling, 11 of expressing opinions, 26 of giving instructions, and 34 of conveying emotions. The findings indicate that alternation is the dominant type of code-mixing, while conveying emotions is the most frequent function. This study contributes to sociolinguistics and digital discourse research by providing empirical evidence of how Indonesian YouTubers strategically employ code-mixing to enhance engagement, express identity, and navigate bilingual communication in online media.